The Microstructure and Dispersive Characteristics of a River Nile Terrace Deposit from Northern Sudan (Journal of Building and Road Research, 2021)
The microstructure of low plastic highly dispersive sandy silty clay (CL) deposit obtained from the terraces of the River Nile in Northern Sudan was studied using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) in relation to its dispersive characteristics. The study showed that the silt size of the CL is mostly aggregates of clay particlescemented by organic matter and iron oxide bonds. Kneading experiments have shown that these aggregates are unstable and could be broken by kneading and compaction. Pinhole tests on specimens prepared at wide ranges of density and water content and kept for different curing times (hours to one year) have shown that neither water content, density andcuring times have pronounced effect on the dispersivity and erosion characteristics of the tested soil.
Keywords: Microstructure; River Nile Terrace Deposit